Alkali-activated concrete paver blocks made with recycled asphalt pavement (RAP) aggregates - Nabil Hossiney; Hima Kiran Sepuri; Mothi Krishna Mohan; Arjun H R; Santhosh Govindaraju; Jorisa Chyne (Case Studies in Construction Materials, 2020)
This study was conducted to evaluate the feasibility of using recycled asphalt pavement (RAP) aggregates in alkali-activated concrete paver blocks. Due to drastic growth in road expansion projects in India, there is tremendous amount of RAP generated by milling and digging of existing bituminous roads. Even though RAP gets recycled in new bituminous roads, there is still large volume of this material that gets downgraded, especially in urban areas. Therefore, there is a need to effectively utilize the unused RAP in paving industry. Alkali-activated paver blocks were synthesized with fly ash (FLA), ground granulated blast furnace slag (GGBS), NaOH sol., Na2SiO3 sol., RAP and natural aggregates. Natural aggregates were substituted with RAP aggregates at replacement rates of 0 %, 25 %, 50 %, and 75 % by weight. The developed paver blocks were tested for water absorption, compressive strength, and abrasion resistance according to IS 15658: 2006 standard. The results of the laboratory study showed that inclusion of RAP aggregates in alkali-activated concrete reduce the compressive strength and abrasion resistance of the paver blocks. Though there is reduction in strength, developed paver blocks classified for use in pedestrian and non-motorized facility. The study also found that the use of RAP aggregates in paver blocks incur economic benefits. A maximum reduction of 25.8 % in production cost was observed for RAP inclusive alkali-activated paver blocks. Furthermore, the proposed method provides environmental benefits by reducing consumption of Portland cement and natural aggregates from quarries, and thus makes paving industry more sustainable and environment friendly.